Lithium toxicity at therapeutic doses as a fallout of COVID-19 infection: a case series and possible mechanisms. (January 2022) - Pai, Naveen Manohar; Malyam, Vidhyavathi; Murugesan, Manisha; Ganjekar, Sundarnag; Moirangthem, Sydney; Desai, Geetha
Abstract : Lithium, a mood stabilizer used in the treatment of bipolar disorder is known for its anti-inflammatory properties with the discussion of its potential use in COVID-19 infection. The SARS-CoV-2 virus causing COVID-19 infection is known to enter the target cells through angiotensin converting enzyme-2 receptors present in abundance in the lung and renal tissue. Recent research supports the evidence for direct renal injury by viral proteins. Here we report two patients with bipolar disorder presenting with lithium toxicity in the presence of COVID-19 infection. Two patients with bipolar disorder, maintaining remission on lithium prophylaxis, presented to the psychiatric emergency with recent-onset fever and altered sensorium. Both the patient's investigations revealed lithium toxicity, elevated serum creatinine, urea and inflammatory markers. Hypernatremia, hyperkalaemia, and hyperchloremia were seen in one patient. Lithium and other psychotropic medications were stopped immediately, and COVID-19 treatment was initiated. Patient with clinical signs of lithium toxicity, hypernatremia, hyperkalaemia, and hyperchloremia developed ventricular tachycardia. He survived and regained consciousness after 2 weeks of aggressive conservative management. However, another patient died of acute respiratory failure on day 3. Possible direct infection of the kidney by SARS-CoV-2 viral proteins can manifest with acute kidney injury and lithium toxicity among patients on long-term lithium therapy. Health professionals treating COVID-19 infection among individuals on lithium therapy should be aware of the possibility of lithium toxicity in the background of renal injury. Abstract : Supplemental Digital Content is available in the text.